2020
DOI: 10.1111/ane.13220
|View full text |Cite
|
Sign up to set email alerts
|

Gamma knife surgery in the treatment of intracanalicular vestibular schwannomas

Abstract: Objective According to the literature, gamma knife surgery (GKS) is a promising method for intracanalicular vestibular schwannoma (IVS) management, providing excellent tumor growth control rates (91%‐100%) and good hearing preservation rates (41%‐76%), but this evidence originates primarily from a small series of patients. The aim of this study was to present the outcomes of GKS in the largest group of patients with IVS studied to date, with particular emphasis on the long‐term outcomes of treatment. Methods T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 46 publications
(124 reference statements)
3
29
0
2
Order By: Relevance
“…Evaluating the volumetric changes in tumor after radiosurgery is an important indicator of response to treatment 2,15 . Some authors reported that tumor control was achieved in 91.1% of the patients followed up approximately 4.5 years after radiosurgery in patients with ICVS 2 . In our study, there was a significant decrease in the tumor volume and a shrinkage in tumor size in 58.82% of the patients treated with ICVS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluating the volumetric changes in tumor after radiosurgery is an important indicator of response to treatment 2,15 . Some authors reported that tumor control was achieved in 91.1% of the patients followed up approximately 4.5 years after radiosurgery in patients with ICVS 2 . In our study, there was a significant decrease in the tumor volume and a shrinkage in tumor size in 58.82% of the patients treated with ICVS.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the true response after radiosurgery, it should be clearly demonstrated whether there is growth in tumor volume by successive follow-up MRIs. It is recommended to be followed up by MRI every 6 months for up to 5 years after radiosurgical treatment 2,8,12,16 .…”
Section: Discussionmentioning
confidence: 99%
“…Bei intrameatalen Vestibularisschwannomen stellen radiochirurgische Therapien wie Gamma-Knife oder CyberKnife etablierte Modalitäten dar, welche in den meisten Fällen eine Tumorkontrolle er-möglichen, gute Chancen eines Hörerhalts haben und nur selten mit Komplikationen verbunden sind [1,3]. Eine operative Versorgung nach radiochirurgischer Vorbehandlung ist nur in wenigen Fällen nötig [9].…”
Section: Diskussionunclassified
“…У 4 пациентов возникла дисфункция лицевого нерва, в том числе 3 эпизодических гемифациальных спазма и 1 частичный парез, которые регрессировали полностью в течение 12 мес после радиохирургического лечения. Ни у одного из пациентов не было выявлено новых неврологических нарушений, в том числе дисфункции тройничного нерва или гидроцефалии [30]. В исследовании A. Niranjan и соавт.…”
Section: Russian Journal Of Neurosurgeryunclassified